North Coast Road to Maracas Bay Trinidad the West Indies - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2009)
A photograph showing the pitch-paved North Coast Road as it winds downhill through a section of Trinidad's Northern Range on the way Maracas Bay. The mountains appear to be a misty blue in the background of the photograph. A few large trees are in the midground. The one that is in the middle of the photograph to the left of the road is a flowerless Poui tree. It's trunk is tall and straight. The pale area to the right of the Poui tree may reveal one of the first glimses of the Maracas Bay one might see, while travelling on this road, before one reaches the bay. Postcard number K-6263.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Roads--Trinidad and Tobago; Trees----Trinidad and Tobago; Bays--Trinidad and Tobago; Coasts--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; Country roads--Trinidad and Tobago; Mountains--Trinidad and Tobago; Flowering trees--Trinidad and Tobago; [1964]; Maracas Bay